Analisis Analisis Perubahan Perilaku Pada Ruang Publik di Kota Balikpapan Dalam Mewujudkan Kota Cerdas - Ratmananda, Diszha; Ulimaz, Mega (LPPM ITK, 2024)
The more a city develops, the higher the need for public space. Balikpapan City is the most populous city in East Kalimantan Province which requires larger public spaces than other cities. The city of Balikpapan has open public spaces and closed public spaces for interaction and activities. In the past, the people of Balikpapan city tended to visit public spaces only as a place to relax and recreate in public green open spaces. As time goes by and public space facilities develop, there are changes in people's behavior that are starting to be seen in line with the development of various activities in public spaces. This can be seen because the aim of current city development is to create various new public spaces following new developments to attract visitors to do activities in them without moving. Therefore, this research aims to determine the highest behavioral changes that occur in public spaces in Balikpapan City using qualitative methods. Data was collected using questionnaires and interviews distributed in public spaces in the city of Balikpapan and analyzed using qualitative descriptive methods to describe open and closed behavior that occurred in public spaces to compare behavior that occurred in public spaces in 2023 and several years earlier. The results of this research show the dominant behavior carried out by people in public spaces, such as gathering, taking photos, making videos, enjoying new facilities provided by public space managers, doing assignments and working. The highest behavioral changes in Balikpapan were in the Super Block and Mall Plaza Balikpapan. This research can be a reference to see the readiness of the community in facing urban development in realizing a smart city through the development of public spaces by taking into account the dominant habits and activities carried out by the community in public spaces.